When Do Clinicians Follow-up Abnormal Liver Tests in Primary Care? - Schreiner, Andrew D. (Am J Med Sci, 2019)
BACKGROUND: Many guidelines addressing the approach to abnormal liver chemistries, including bilirubin, transaminases, and alkaline phosphatase, recommend repeating the tests. However, when clinicians repeat testing is unknown. METHODS: This retrospective study followed adult patients with abnormal liver chemistries in a patient-centered medical home (PCMH) from 2007 to 2016. All PCMH patients possessing at least one abnormal liver test (total bilirubin, aminotransferases, and alkaline phosphatase) were included. Patients were followed from the index abnormal liver chemistry until the next liver test result, or the end of the study period. The primary predictor variable of interest was the number of abnormal chemistries (out of 4) on index testing. Demographic and clinical variables served as other potential predictors of outcome. A Cox proportional hazards model was applied to investigate associations between the predictor variables and the time to repeat liver chemistry testing. RESULTS: Of 9,545 patients with at least 2 PCMH visits and 1 liver test abnormality, 6,489 (68%) obtained repeat testing within 1 year, and 80% of patients had follow-up tests within 2 years. Patients with multiple abnormal liver tests and those with higher degrees of abnormality were associated with shorter time to repeat testing. CONCLUSIONS: A large proportion of patients with abnormal liver tests still lack repeat testing at 1 year. The number of liver tests abnormal and degree of elevation were inversely associated with the time to repeat testing.